Actual approaches to assessing the economic efficiency of using the intellectual activity results - S. A. Polukhina; E. A. Nikiforova (Путеводитель предпринимателя)
The article discusses modern approaches to assessing the effectiveness of the use of intellectual property. The criteria for recognizing the results of intellectual activity in accordance with the legislation of the Russian Federation and international financial reporting standards are defined. The economic characteristics of the intangible assets of the enterprise are given. The principles of determining the value of intellectual property objects are presented. The main directions of the use of intangible assets for the purposes of the activity of an economic entity are formulated. Approaches to the definition of economic results from the introduction of the results of intellectual activity into economic circulation are proposed.